Influence of Business Management on Finance: Case Study Peru (LACCEI, 2024)
The present work of investigation has for objective to describe the influence of the enterprise Management in the finances of the company Alexander Express L M S.A.C., Trujillo 2019-2020, since it has been seen that the company has had a planning for his economic growth executing an optimal management that has offered him favourable results. This research is of type Quantitative applied experimental design of non-cross-sectional cut and descriptive scope, with a population of research study element to the company Alexander Express L M S.A.C., and as a sample focused on staff who are related to the management of business management and finance of the company. As collection techniques used the interview and documentary analysis, which resulted in the company according to the ratios of liquidity, management and profitability reflects that manages its finances for any investment in the short and long term, according to its financial statements the company has liquidity to cover any investment with third parties, as a conclusion was obtained that the company there is a business management that positively influences the finances of the company.